Ground state of naphthyl cation: singlet or triplet? - Dutta, Achintya Kumar; Manohar, Prashant Uday; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2014)
We present a benchmark theoretical investigation on the electronic structure and singlet- triplet(ST) gap of 1- and 2-naphthyl cations using the CCSD(T) method. Our calculations reveal that the ground states of both the naphthyl cations are singlet, contrary to the results obtained by DFT/B3LYP calculations reported in previous theoretical studies. However, the triplet states obtained in the two structural isomers of naphthyl cation are completely different. The triplet state in 1-naphthyl cation is (pi,sigma) type, whereas in 2-naphthyl cation it is (pi,sigma) type, The S-T gaps in naphthyl cations and the relative stability ordering of the singlet and the triplet states are highly sensitive to the basis set quality as well as level of correlation, and demand for inclusion of perturbative triples in the coupled-cluster ansatz. (c) 2014 AIP Publishing LLC.